OMNICHANNEL RETAILING AND CONSUMER DECISION IN BEAUTY PRODUCTS: SOCIOLLA’S EXPERIENCE - Fernanda, Nathasya; Wibowo, Wahyudi; Sutedjo, Purnomohadi (Kesatuan Press, 2025)
This study investigates the influence of omnichannel experiences on the repurchase intention of beauty products, with customer satisfaction and trust serving as mediating variables. The study's data were gathered via an online poll of 180 participants in Indonesia. The survey results were examined using Structural Equation Modeling techniques with SmartPLS 3.0. The findings confirm that omnichannel experiences directly influence repurchase intention, customer satisfaction, and trust in the beauty product purchasing process. Furthermore, trust and customer satisfaction mediate The relationship between consumers' repurchase intentions and omnichannel experiences.